Use of a microbial nexus system in high andean areas: effectiveness and feasibility for wastewater treatment - Hualpa Cutipa, Edwin (2024)
High altitudes harbor several microbial species with unique properties, mainly because of their climatic and geographic characteristics that limit their adaptation. At present, several environmental problems are endangering the health of our planet, among which the pollution of aquatic ecosystems is one of the most important. Wastewater from various industries is treated before being released into the environment, but the strategies used are insufficiently effective, causing environmental problems. New methodologies have been proposed that are based on the implementation of microbial niches that are associated with wastewater treatment systems. Searching for microorganisms in native environments is an important step in establishing new microbial niches related to wastewater treatment. This is mainly because these indigenous microorganisms possess very versatile characteristics, which can be exploited to improve the efficiency of treating wastewater. A specific microbial community is used to degrade pollutants at each stage of biological wastewater treatment. To ensure the efficiency and effectiveness of the treatment process, the coupling of microbial niches in wastewater treatment is essential. In addition, this technique is more economical and environmentally friendly than other alternatives. This makes it an attractive option for wastewater treatment. Thus, this chapter attempts to address the main advantages of using microbial niches inhabiting the high Andean areas and their integration in wastewater treatment. In addition, new strategies will be proposed to study and recover these native microbes with high genetic value for application in different pollutant treatment systems.